A new framework for horticultural research in botanic gardens and arboreta of the United States - Opgenorth, Michael; Ávila, Julia; Bryce, Sarah; Rae, David; Rønsted, Nina (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2025)
Botanic gardens and arboreta maintain globally important collections for conservation and education. Many organisations hold a reputation for excellence in propagation, cultivation and collection preservation. Learning from successes and challenges, and having the ability to disseminate that knowledge, is paramount for improving techniques and outcomes. However, the field of horticultural research is not well defined, and results of plant cultivation techniques are often only shared informally rather than published. This study was designed to explore how horticultural research practitioners perceive the field of horticultural research and excellence, how they and their institutions are involved, and what are the most urgent needs of future horticultural research among gardens and arboreta in the United States. An online survey was distributed to ascertain the status of horticultural research amongst the United States members of the American Society for Horticultural Science, the American Public Gardens Association, Botanic Gardens Conservation International and the Interactive Community of Arboreta, Level II, III and IV members. The survey was completed by 128 respondents from 34 US states across 116 institutions. The responses highlight the fact that horticultural excellence is holistic – focusing on species conservation, ecology and pest mitigation. The findings also touch on the status and involvement of respondents in horticultural research and their perceived needs for future research. These responses further highlight challenges such as funding, time and personnel shortfalls. Horticultural research also includes an emphasis on practical approaches, requiring better recognition and sharing methods. The findings introduce a new framework to support the horticulture community in conceptualising, communicating and implementing research. This framework proposes that horticultural research can be broadly categorised into two overarching approaches: practical and technical.